Aerobic biodegradation of precoagulated cheese whey wastewater - Rivas, Javier (2011)
Prior to the application of an aerobic biological process, cheese whey wastewater has been pretreated by means of a precipitation stage by adding either NaOH or CaOH2. Both precipitating agents reduce roughly 50% of the raw wastewater chemical oxygen demand (COD). The sludge generated in the prestage shows acceptable settling properties, although solids from the CaOH2-treated effluent are better separated from the liquid bulk than those formed in NaOH-processed wastewater. In both situations, the presedimentation stage renders a supernatant more prone to biodegradation than the untreated effluent. The previous statement is corroborated by the determination of some biological kinetic parameters. Under the operating conditions used in this work, sludge generation after the biological process is reduced to a minimum. The sludge generated shows good settling properties, especially for those experiments in which CaOH2 has previously been added.